Low‐Magnitude Mechanical Stimulation to Improve Bone Density in Persons of Advanced Age: A Randomized, Placebo‐Controlled Trial. (July 2015) - Kiel, Douglas P; Hannan, Marian T; Barton, Bruce A; Bouxsein, Mary L; Sisson, Emily; Lang, Thomas; Allaire, Brett; Dewkett, Dawn; Carroll, Danette; Magaziner, Jay; Shane, Elizabeth; Leary, Elizabeth Teng; et al.
Abstract Nonpharmacologic approaches to preserve or increase bone mineral density (BMD) include whole‐body vibration (WBV), but its efficacy in elderly persons is not clear. Therefore, we conducted the Vibration to Improve Bone in Elderly Subjects (VIBES) trial, a randomized, placebo‐controlled trial of 10 minutes of daily WBV (0.3g at 37 Hz) in seniors recruited from 16 independent living communities. The primary outcomes were volumetric BMD of the hip and spine measured by quantitative computed tomography (QCT) and biochemical markers of bone turnover. We randomized 174 men and women (89 active, 85 placebo) with T‐scores –1 to –2.5 who were not taking bone active drugs and had no diseases affecting the skeleton (mean age 82 ± 7 years, range 65 to 102). Participants received daily calcium (1000 mg) and vitamin D (800 IU). Study platforms were activated using radio frequency ID cards providing electronic adherence monitoring; placebo platforms resembled the active platforms. In total, 61% of participants in the active arm and 73% in the placebo arm completed 24 months. The primary outcomes, median percent changes (interquartile range [IQR]) in total volumetric femoral trabecular BMD (active group (2.2% [–0.8%, 5.2%]) versus placebo 0.4% [–4.8%, 5.0%]) and in mid‐vertebral trabecular BMD of L1 and L2 (active group (5.3% [–6.9%, 13.3%]) versus placebo (2.4% [–4.4%, 11.1%]), did not differ between groups (all p values > 0.1). Changes in biochemical markers of bone turnover (P1NP and sCTX) also were not different between groups (p = 0.19 and p = 0.97, respectively). In conclusion, this placebo‐controlled randomized trial of daily WBV in older adults did not demonstrate evidence of significant beneficial effects on volumetric BMD or bone biomarkers; however, the high variability in vBMD changes limited our power to detect small treatment effects. The beneficial effects of WBV observed in previous studies of younger women may not occur to the same extent in elderly individuals. © 2015 American Society for Bone and Mineral Research.